Pengaruh Pelatihan Kerja, Motivasi Dan Stres kerja Terhadap Produktivitas kerja Pada PT. Nittoh Batam - vernando, Alfis; Purba, Daris (SCIENTIA JOURNAL, 2021)
This study aims to determine and analyze whether there is an effect of job training, motivation, and work stress on the work productivity of nittoh batam. In this research, the type of research used is quantitative research, the sampling technique uses a saturated sample of 151 respondents, the data obtained is then processed using the SPSS version 22 statistical application then the research results are obtained for t count 4.041> 1.97612 significance 0.000> 0.05 so training work has a positive and significant impact on work productivity. Motivation to get the results of t count 4.265> 1.97612 at a significance value obtained 0.000 3.06 (F table) with a significance of 0.000 <0.05.. Keywords: Job training, motivation, work stress and work productivity